Land management in the Conata Basin: a free market approach. Issue 1 (9th February 2015) - Bahun, Joseph; Block, Walter E.
Abstract : Purpose: – The purpose of this paper is to demonstrate the viability of free market environmentalism. This is the philosophy that has as its basic premise the view that laissez faire capitalism and concomitant private property rights, far from being an impediment to the well-functioning of the environment, are actually the last best hope for this desiderata. Design/methodology/approach: – The prairie dog and the ferret are not the species usually associated with concern over endangerment. Typically, it is the whale, the elephant and the rhino that are subjected to such an analysis. The authors approach this issue through the "eyeglasses" of the economist who sees value in our free enterprise institutions. Findings: – The authors found that the tragedy of the commons works in this case as it does in all other relevant venues: if land is not privately held, but rather open to all, a tragedy occurs: there is economics misallocation and a too swift use of resources compared to the optimal situation. Originality/value: – The authors know of no other examination of the prairie dog and the ferret in the Conata Basin. This is an important case in point in amassing evidence of the workings of the private property system vis-à-vis the environment.